Experiences of Outcome Monitoring in the CGIAR - Immonen, S.; Fischer, K. (CGIAR Independent Science and Partnership Council, 2012)
This paper presents a summary of the characterization and analysis of the observations and results over the five years of the Performance Measurement System when outcome cases were recorded. Lessons are drawn from the PMS experience for designing monitoring of results of the CRPs.